Differentiated cytoplasmic granule formation in quiescent and non-quiescent cells upon chronological aging - Hsin-Yi Lee; Kuo-Yu Cheng; Jung-Chi Chao; Jun-Yi Leu (Microbial Cell)
Stationary phase cultures represent a complicated cell population comprising at least two different cell types, quiescent (Q) and non-quiescent (NQ) cells. Q and NQ cells have different lifespans and cell physiologies. However, less is known about the organization of cytosolic protein structures in these two cell types. In this study, we examined Q and NQ cells for the formation of several stationary phase-prevalent granule structures including actin bodies, proteasome storage granules, stress granules, P-bodies, the compartment for unconventional protein secretion (CUPS), and Hsp42-associated stationary phase granules (Hsp42-SPGs). Most of these structures preferentially form in NQ cells, except for Hsp42-SPGs, which are enriched in Q cells. When nutrients are provided, NQ cells enter mitosis less efficiently than Q cells, likely due to the time requirement for reorganizing some granule structures. We observed that heat shock-induced misfolded proteins often colocalize to Hsp42-SPGs, and Q cells clear these protein aggregates more efficiently, suggesting that Hsp42-SPGs may play an important role in the stress resistance of Q cells. Finally, we show that the cell fate of NQ cells is largely irreversible even if they are allowed to reenter mitosis. Our results reveal that the formation of different granule structures may represent the early stage of cell type differentiation in yeast stationary phase cultures.